How Micro-Influencers Influence the Evolution of Brand Engagement: Insights from a Literature Review - Tammy Mcclellan; Eka Farida; Bambang Banu Siswoyo (Escalate : Economics and Business Journal, 2025)
This systematic literature review explores the strategic role of micro-influencers in shaping brand engagement within digital marketing ecosystems. Analyzing 61 peer-reviewed articles published between 2019 and 2024, the study synthesizes key insights across ten thematic areas including influencer strategy, consumer trust, emotional connection, and technological adaptation. Findings reveal that micro-influencers foster deeper consumer interactions than macro-influencers due to their authenticity, consistent storytelling, and alignment with niche communities. Additionally, platform-specific features and ethical messaging enhance consumer trust and brand loyalty. The study proposes a conceptual framework for understanding micro-influencers as co-creators of brand meaning and highlights implications for relationship marketing. This research offers both theoretical advancement and practical guidance for brands navigating an increasingly fragmented digital landscape.